A beam‐switchable low‐profile antenna based on substrate integrated waveguide. Issue 9 (15th November 2018) - Jiang, Zhen‐Hua; Su, Tao; Hou, Jian‐Qiang
Abstract: In order to improve the communication quality in mobile applications, a low profile pattern reconfigurable printed patch antenna is designed. The design of the radiating structure is based on the study of the field distribution of the quarter mode substrate integrated waveguide. The proposed antenna is fed by four coaxial feed ports. Compared with the most patch antennas that only produce axial beam patterns, the proposed antennas can generate different beams by simply changing the excitation methods. The antenna can generate a total of 12 beams to meet the needs of different application scenarios conveniently. In addition, isolation between ports is improved by introducing SRR and CSRR structures. Simulation and measurement results show good agreement, the antenna can obtain stable gain of more than 5dBi in the direction of the main beam. The antenna is designed to operate at 2.45 GHz. It has a height of 1.5 mm, so its profile is low.